Development of digital optical switch for all optical cross-connect - Mohd. Supaat, Abu Sahmah (Faculty of Electrical Engineering, 2008)
In terms of performance, communication by optical fiber is potentially the most rewarding of all communications. It has been suggested that if the full potential of fiber optic communication is realized, a single fiber would be sufficient to serve the needs of telecommunication users (heavy data traffic demands) throughout the world. Fiber optics is the channeled transmission of light through hair thin glass. The explosive growth of optical networks has brought forward an increased need for guided wave optical components for the sake of multiplexing and routing. Beam splitters are a basic element of many optical fiber communication systems often providing a Y-junction by which signals separate sources can be combined, or the received power divided between two channels. The purpose of this project is to investigate how an asymmetric Y-junction behaves as an optical switch using switching function called Thermo Optic Effect. The focus is made on the polymers used for making various layers of waveguide, geometry and design parameters of waveguide which make it better than other Y-splitters. Polymers are relatively cheap starting material and can be processed from solution, which offers additional potential for cost savings compared to other technologies and also have the advantage of having large thermo optic coefficient range. The polymers used are polyurethane (thermal coefficient: -3.3 x 10-4 K-1, thermal conductivity: -0.19 W m-1K-1) and PMMA (thermal coefficient: -1.2 x 10-4 K-1, thermal conductivity: -0.17 W m-1K-1). The 2D thermal analysis is made on buried type waveguide. The analysis is based on how heating of one of the arms change its refractive index leading to low crosstalk, insertion loss, low driving power, coupling length and optimum switching characteristics. All simulations are done using BPM (Beam Propagation Method) and FEMLAB (Finite Element Method) software. The results from this project is a structure of Y-junction digital optical switch which is compact in size, less power consumption, low crosstalk and insertion loss by varying various parameters like branching angle, spacing between the two arms of Y-junction, refractive index change of one of the arms by means of heating phenomenon and switching temperature.